Empowering professional learning communities of secondary science teachers to uncover and address their students’ misconceptions via research-oriented practices - Potvin, Patrice; Boissard, Bénédicte; Durocher, Éric; Hasni, Abdelkrim; Riopel, Martin (Frontiers in Education, 2024)
The Partnership for the Development and Success of Science Education in Secondary Schools project seeks to improve science education by fostering a dynamic environment for professional development and teacher-led inquiry within professional learning communities (PLCs). Addressing the long-standing problem of outdated pedagogical approaches, the initiative encourages secondary science teachers to actively engage in action research to identify and/or address student misconceptions of scientific concepts. Through collaboration with professional development leaders and university experts, teachers are empowered to implement and refine evidence-based instructional strategies and cultivate a culture of ongoing professional growth and reflective practice. The partnership emphasizes the importance of bridging the gap between educational research and classroom practice to improve the quality and effectiveness of science education. The project aims to bring about a positive change in teachers' instructional practices and reflections and an increased alignment with contemporary educational standards and evidence-based practices.